An experimental study of investigating the relationships between structures and properties of al alloys included with high Mg and high Ti - (:unkn) unknown (INDERSCIENCE ENTERPRISES LTD, 2018)
In this study, the influences of high magnesium (Mg) and high titanium (Ti) additions on aluminium (Al) alloys were investigated to peruse the relationship between the structure and properties of the new alloys. Microstructural analyses were performed using X-ray diffraction (XRD), the polarised optical microscope, and scanning electron microscope (SEM) equipped with energy dispersive spectrometry (EDS). In the microstructure of the alloys, the beta-phase (Al3M2) alpha-solid solution, Ti2Mg3Al18 and TiAl3 particles were revealed. Results showed that the average grain size of Al-Mg-Ti alloys was found to be different in each composition, and the smallest grain size was obtained at Al-12Mg-3Ti alloy as 88 mu m. The highest tensile strength (170 MPa) was attained with additions of 8 wt.% Mg and 1 wt.% Ti, but the highest hardness value (125 HBN) was obtained with additions of 14 wt.% Mg and 3 wt.% Ti. It was noted that the smallest average grain size did not behave in accordance with the highest mechanical properties. For the work, the optimal ratios of magnesium and titanium entrained into Al alloys were 8 wt.%, and 1 wt.%, respectively.
Keywords: Ti and Mg additions; Al-Mg-Ti alloys; microstructure; mechanical and physical properties; casting; MECHANICAL-PROPERTIES; GRAIN-REFINEMENT; TENSILE PROPERTIES; HETEROGENEOUS NUCLEATION; MASTER ALLOYS; WEAR BEHAVIOR; ALUMINUM; MICROSTRUCTURE; ZN; CU